Analysis of the Effect of Income on the Consumption Patterns of Mining Workers in Watusampu Subdistrict - Rescky Putra Ramadhan; Andi Herman Jaya; Eko Jokolelono; Mukhtar Tallesang; Armin Armin (Transpublika Publisher, 2025)
The mining industry in Watusampu Subdistrict boosts local incomes but also brings socio-economic and environmental challenges. Mining provides jobs and higher wages but causes environmental degradation and air pollution leading to health issues. This study aims to analyze the influence of income on consumption patterns of workers in the mining sector in Watusampu Subdistrict. This sector has unique characteristics, especially regarding worker income levels, which can influence spending patterns. The method used in this research is quantitative with a survey approach, involving a sample of workers from various job levels in a mining company. Using simple linear regression analysis tools, this study explains the influence of income on consumption, both for food and non-food goods, among mining sector workers in Watusampu Subdistrict. The research results show that income has a positive and significant influence on expenditures for food and non-food items. Based on the research results, the regression equations obtained are: Y = 230,543.653 + 0.258X, Y = 170,503.477 + 0.361X, Y = 922,634.574 + 0.329X, Y = 212,953.571 + 0.557X. The regression coefficients indicate that income increases will increase expenditures, with a larger proportion directed toward non-food goods.